1999
DOI: 10.1046/j.1365-2982.1999.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastrin on proximal gastric motor function in humans

Abstract: gastrin may have a role in regulating proximal gastric mechanics by inducing fundic relaxation and increasing gastric wall compliance. The effect of gastrin is dependent on acid secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…The investigators found that infusion of ghrelin increased gastric emptying in insulin-requiring diabetic patients with gastroparesis and that this effect was independent of vagal tone. Cholecystokinin (CCK) and gastrin also have been shown to be effective in treating severely delayed gastric emptying [110,111]. Excellent reviews of gastroparesis and its potential treatments are available in the literature [83,106,112,113].…”
Section: Current Therapies For Gastric Emptying Disordersmentioning
confidence: 98%
“…The investigators found that infusion of ghrelin increased gastric emptying in insulin-requiring diabetic patients with gastroparesis and that this effect was independent of vagal tone. Cholecystokinin (CCK) and gastrin also have been shown to be effective in treating severely delayed gastric emptying [110,111]. Excellent reviews of gastroparesis and its potential treatments are available in the literature [83,106,112,113].…”
Section: Current Therapies For Gastric Emptying Disordersmentioning
confidence: 98%
“…Vagal afferents transmit both physiological stimuli (gastrin) and pathological events (back diffusion of luminal HCl or NH 4 OH) from the stomach to the brain stem. 40 It has been reported that duodenal acidifi cation has an inhibitory effect on gastric emptying, [41][42][43][44][45] and HCl may restrict gastric outfl ow by inducing tonic occlusion of the duodenum. 45 We included one H. pylori-positive subject as a healthy control in this study because he had no dyspeptic symptoms and no organic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1967, Hunt and Ramsbottom [55] reported the slowing of gastric emptying in 2 humans during an intravenous infusion of gastrin. The effect of gastrin on interdigestive antroduodenal motility and intragastric volume (increase) seems to be mediated by the associated increase of intraluminal acidity [56,57]. On the other hand, intravenous amino acids increased intragastric volume without a notable increase in plasma gastrin.…”
Section: Amino Acids In Regulation Of Stomach Emptyingmentioning
confidence: 96%
“…In an above-mentioned human study, intravenous infusion of gastrin increased the intragastric volume and compliance in healthy volunteers. Symptom perception decreased during gastrin infusion [57]. In another volunteer study (Straathof et al [51]), infusion of CCK at doses resulting in plasma levels in the (peak) postprandial range induced gastric fundal relaxation and increased compliance of the gastric walls.…”
Section: Pepsin-induced Processes Supportive Of Digestionmentioning
confidence: 98%